Template effect of single/double-chain quaternary ammonium salts on the formation of mesoporous ZrO2 nanomaterials. Issue 9 (15th June 2017) - Wang, Huigang; Yu, Feng; Su, Jiaojiao; Shi, Guoliang; Pan, Dahai; Li, Ruifeng
Abstract: A double-chain quaternary ammonium salt of dioctyl dimethyl ammonium chloride (DDAC8) was first used as a low-cost template to prepare the mesostructured zirconia nanomaterials in an alcohol-thermal system. The material was calcinated to obtain pure tetragonal crystalline zirconia ( t -zirconia) and thus has significantly improved original structure properties, including a narrow pore size distribution of 4–7 nm and a high surface area of 195 m 2 /g. The t -zirconia hierarchical nanoparticle aggregate material is different from the smooth microsphere material obtained using the single chain quaternary ammonium salt template. The characteristic rough surface morphology results from the grid distribution form of the DDAC8 micelles in the ethanol solution and caused the formation of more defect sites, which demonstrate the potential for possible catalytic applications. A formation mechanism of the mesoporous zirconia nanomaterial in the alcohol-thermal system of the surfactants is reasonably explained. The synthesis system may provide a new approach to the preparation of mesoporous nanomaterials.